2009
DOI: 10.1016/j.jpor.2009.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Differences in masticatory function of subjects with different closing path

Abstract: From these results, it was suggested that there was a functional difference between Group I (with a convex closing path) and Group II (with a concave closing path), and that Group I had a superior masticatory function to Group II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The present method was simple and acceptable for use in a clinical patient setting, as the specimens had characteristics similar to typical sweets that contain glucose. In a previous study, the present method for masticatory efficiency was validated and found to be comparable to a sieve method [40]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present method was simple and acceptable for use in a clinical patient setting, as the specimens had characteristics similar to typical sweets that contain glucose. In a previous study, the present method for masticatory efficiency was validated and found to be comparable to a sieve method [40]. …”
Section: Discussionmentioning
confidence: 99%
“…The amount of glucose extraction in the filtrate obtained after chewing the specimen was used as a measure of masticatory efficiency. Glucose concentration in the filtrate (mg/dl) was measured using a calibrated Glucose Sensor Set (Glucosensor GS-1, GC, Tokyo, Japan), which utilizes a glucose sensor for diabetics (Accu-check Comfort, Roche Diagnostic, Basel, Switzerland) to measure masticatory efficiency according to a previous study, which reported its reliability for the evaluation of masticatory function [40]. For reproducibility, we tested the glucose concentration of control glucose solutions (500, 250, 125, 100, and 50 mg/dl) with the glucose sensor.…”
Section: Methodsmentioning
confidence: 99%
“…Kobayashi et al . reported that different closing paths during mastication affect masticatory performance, which related to strength of activities of perioral muscles such as masseter or temporal muscle. Additionally, it has been suggested that oral sensitivity is associated with masticatory performance.…”
Section: Discussionmentioning
confidence: 99%
“…function. Previous studies have used different materials, with distinct characteristics, number of particles, size and weight, for analysis, such as wine gum, almond, paraffin, wax cube, gummy jelly (4)(5)(6)(7)(8), while the present study used cubes made of a rubber based artificial material. It has been reported that chewing cycle alters its pattern according to the hardness or the size of bolus (3) and to the rheological properties of the food (15), suggesting the reason for such divergence of data.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some other parameters of mandibular movement, such as vertical amplitude, cycle duration and closing duration, were significant correlated with food mixing ability, being the former a positive and the other 2 parameters, negative correlations (5). The closing path was also associated to quality of mastication, being the closing angle negatively correlated with food mixing ability (5) and a convex closing path related to better masticatory function (6). Similar results were reported by Lepley et al (7), who found a more horizontal path of cycle closure among better masticatory performers rather than in poorer chewers.…”
Section: Introductionmentioning
confidence: 98%